Systematic Literature Review on The Use of Gamification Approaches in Mastering the Periodic Table of Elements (Chemistry) - Suzinursolahah binti Saleh; W Omar Ali Saifuddin Wan Ismail (International Journal of Educational Narratives, 2024)
Background: Gamification applications serve as tools for students to independently construct knowledge about lesson content, potentially surpassing achievements gained through conventional methods. The study of gamification is especially important for learning the Periodic Table of Elements, a fundamental topic in chemistry. Purpose: This article aims to explore the application of gamification in learning the Periodic Table of Elements between 2019 and 2023. Methods: A systematic literature review was conducted using online databases such as Scopus and Web of Science to gather relevant information on the subject. Keywords like "Periodic Table," "Teaching Approach," and "Gamification" were used to search for studies related to the topic. The review included literature from 14 countries: Pakistan, Indonesia, Japan, Spain, the United States, Macedonia, Israel, Morocco, Brazil, Portugal, Croatia, Mexico, and Malaysia. Results: The review focused on identifying commonly used gamification methods and assessing the impact of gamification on motivation, academic achievement, and usability. The findings revealed that board games, digital cards, puzzles, and Virtual Labs were the main gamification approaches used. A comprehensive analysis of 18 literature review articles showed that motivation was the primary impact studied in mastering the periodic table using gamification. Conclusions: This study has significant implications for Chemistry teachers, STEM researchers, and the Teacher Education Division in Malaysia’s Education Ministry. By understanding learners’ preferences, educators can tailor their instructional methods to better meet students’ specific needs.